Pride and profit : the intersection of Jane Austen and Adam Smith - Bohanon, Cecil E.; Vachris, Michelle Albert (Capitalist thought: studies in philosophy, politics, and economics., 2015)
Pride and Profit explores the ways in which Jane Austen's novels interact with the ideas of economist Adam Smith. Bohanon and Vachris show how Smithian perspectives on virtue are depicted in Austen's novels and how Smith's and Austen's perspectives reflect and define the bourgeois culture of the Enlightenment and industrial revolution.